Numerical investigations on an improved counterflow double-channel micro combustor fueled with hydrogen for enhancing thermal performance - Zuo, Wei (2020)
In this work, an improved counterflow double-channel micro combustor is designed. Computational Fluid Dynamics software Fluent is used to conduct numerical investigations on the thermal performance comparison between the old and improved counterflow double-channel micro combustors. It is found that the improved counterflow double-channel micro combustor has much higher and more uniform wall temperature compared that of the old one under various hydrogen mass flow rates, hydrogen/air equivalence ratios and solid materials. To make a quantitative comparison, the main results are presented as follows: (a) The improved combustor achieves the largest thermal enhancement at the hydrogen mass flow rate of 5.25 × 10−7 kg/s when the hydrogen mass flow rate is ranged from 5.25 × 10−7 kg/s to 9.8245 × 10−7 kg/s. Namely, the mean temperature of upper and right wall is improved by about 9.66 K and 13.53 K, respectively, and the mean nonuniformity of upper and right wall temperature is reduced by about 23.24% and 26.79%, respectively. (b) The improved combustor achieves the largest thermal enhancement at the hydrogen/air equivalence ratio of 0.6, when the hydrogen/air equivalence ratio is ranged from 0.9 to 0.5. Namely, the mean temperature of upper and right wall is improved by about 27.55 K and 29.55 K, respectively, and the mean nonuniformity of upper and right wall temperature is reduced by about 23.24% and 19.51%, respectively. (c) The improved combustor achieves the largest thermal enhancement at the solid material of silicon carbide when the solid material is changed from quartz to silicon carbide. Namely, the mean temperature of upper and right wall is improved by about 16.77 K and 18.38 K, respectively, and the mean nonuniformity of upper and right wall temperature is reduced by about 26.47% and 28.41%, respectively. Finally, some guidelines are proposed for applications of the improved counterflow double-channel micro combustor in the micro-thermophotovoltaic system.